Preventing Debtor Bankruptcy during the Covid-19 Pandemic: Benefits of Suspension of Debt Payment Obligations & Insolvency Test? - Kendry Tan (Fakultas Hukum, Universitas Internasional Batam, 2022)
The Covid-19 caused a decline in the Indonesian economy, thus increasing bankruptcy cases in Indonesia. The number of bankrupt companies during the Covid-19 pandemic will result in further decline in the Indonesian economy. Postponement of Debt Payment Obligations is needed to reduce bankruptcy in Indonesia during this pandemic. This study aims to explain the benefits of Postponing Debt Payment Obligations and Insolvency Tests during the Covid-19 pandemic in maintaining Indonesia's economic stability. This research is using the method of juridical normative by using the data secondary as a reference in conducting research. The results of the research are that Postponement of Debt Payment Obligations has important benefits in avoiding bankruptcy for solvent debtors with good intentions during the pandemic to avoid individuals who take advantage of this condition to bankrupt their debtors and insolvency tests have an important role in reducing errors in determining bankruptcy case or Postponement of Debt Payment Obligations by stating their ability to pay.